Whole-Transcriptome Analysis Reveals Long Noncoding RNAs Involved in Female Floral Development of Hickory (Carya cathayensis Sarg.) - Li, Caiyun; Jin, Hongmiao; Zhang, Wei; Qin, Tao; Zhang, Xin; Pu, Zhenyang; Yang, Zhengfu; Lim, Kean-Jin; Wang, Zhengjia (Frontiers in Genetics, 2022)
Hickory, an endemic woody oil and fruit tree species in China, is of great economic value. However, hickory has a long juvenile period and an inconsistent flowering of males and females, thus influencing the bearing rates and further limiting fruits yield. Currently, it is reported that long noncoding RNAs (lncRNAs) play critical regulatory roles in biological processes. However, the role of lncRNAs in the development of hickory female flowers remains unclear. In this study, a total of 6,862 putative lncRNAs were identified from the female flower transcriptomes in three different growth stages of hickory. We proposed that lncRNAs might play an important role in phytohormone signaling processes for flower formation, especially in the abscisic acid and jasmonic acid pathways, according to the results of our Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. Moreover, we predicted the interactions among four microRNAs (miRNAs), three lncRNAs, and four genes. We proposed that facing the changing environment, LNC_002115 competes with PHOSPHATE2 (PHO2) for the binding sites on cca-miR399f, and protects PHO2 from suppression. In addition, cis-acting LNC_002115 regulates the expression of the SHORT VEGETATIVE PHASE (SVP) by influencing ABRE-binding factor (ABF). In brief, LNC_002115 regulates hickory female floral development by impacting both PHO2 and SVP. This study was the first to identify lncRNAs involved in hickory female floral development, and provided new insight to elucidate how lncRNAs and their targets play a role in female floral development in hickory, thus unfolding the opportunities for functional characterization of blossom-related lncRNAs in further studies.